2017
DOI: 10.18870/hlrc.v7i1.367
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Students with Accommodations and Instructor Self-Efficacy in Complying with Accommodations

Abstract: <p>The willingness and flexibility of university instructors to comply with and provide accommodations for students with disabilities is critical to academic success. The authors examine how communication between students needing accommodations and university instructors impacts instructor self-efficacy, or instructors’ perception that they can meet the accommodation. Specifically, the authors’ explored the relationship between student self-disclosure of a disability and instructor empathy, flexibility, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…According to Rahman (2010), students are able to understand their potential through career guidance by recognizing their interests, talents, attitudes, skills, and aspirations, and aims to increase students' knowledge and self-efficacy. Furthermore, Wright and Meyer (2017) say that career guidance is very important for students' academic success. Based on these findings, career guidance can shape student self-efficacy for the better.…”
Section: Hypotheses Testingmentioning
confidence: 99%
“…According to Rahman (2010), students are able to understand their potential through career guidance by recognizing their interests, talents, attitudes, skills, and aspirations, and aims to increase students' knowledge and self-efficacy. Furthermore, Wright and Meyer (2017) say that career guidance is very important for students' academic success. Based on these findings, career guidance can shape student self-efficacy for the better.…”
Section: Hypotheses Testingmentioning
confidence: 99%
“…In agreement with [23], university instructors' willingness and flexibility to comply with and provide accommodations for students with disabilities is critical to academic success.…”
Section: University Instructors For Students With Disabilities Using mentioning
confidence: 99%
“…Training also needs to address communication strategies instructors can use to support students. Wright and Meyer (2017) examined student self-disclosure about accommodations and found that higher self-disclosure led to higher self-efficacy on the part of the instructors in making the accommodations. The implications of this are twofold.…”
Section: Strategies For Addressing Mental Health Stigmamentioning
confidence: 99%
“…If instructors communicate that their classroom is a stigma-free environment from the first day of class, students may feel more comfortable disclosing. Second, while Wright and Meyer (2017) note that instructors are legally bound to give students "the benefit of the doubt that the accommodations are necessary" (p. 77), they also suggest that instructors may "ask the students if they are comfortable providing more context regarding the need for an accommodation, or take time to gather more information about the disability on their own" (p. 77). If instructors can convey immediacy and approachability toward students while proactively creating a climate that eliminates stigmas, they may find themselves in a more self-efficacious situation when making accommodations.…”
Section: Strategies For Addressing Mental Health Stigmamentioning
confidence: 99%